Proposal for the adaptation of the teaching-learning process to the virtual modality in the orthodontics specialty - Liuba González Espangler (Centro Provincial de Información de Ciencias Médicas, 2021)
At the moment, the present forms of the teaching-learning process in orthodontics have been affected by the world epidemiological situation. To such effects we propose an alternative for the adaptation of this process from a virtual environment, is proposed. The first year of the specialty was selected, because it is more complex as for this modality. In this proposal the forms of organization of the teaching, abilities and evaluation that can be carried out in the virtual classroom are shown. Also, some alternatives are offered for filling in the abilities card. This proposal includes the performance of most of the essential aspects to reach for this level, which could guarantee the continuity of the professional training able to solve health problems in an independent and creating way.